Strategic Delegation and Mergers in Oligopolistic Contests - Matthias Kräkel; Dirk Sliwka (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
In this paper, we combine the strategic delegation approach of Fershtman-Judd-Sklivas with contets. The results show that besides a symmetric equilibrium there also exist asymmetric equilibria in which one owner induces pure sales maximization to his manager so that all the other firms drop out of the market. If merging is allowed on an initial stage, the resulting merged subgame perfect equilibria show that there is strictly more merging under contest than under Cournot competition. We also compare our findings with the previous results on contest models with delegation and find that the outcomes for the Fershtman-Judd-Sklivas incentive scheme clearly differ. Especially, in our model we have a prisoner`s-dilemma like situation where delegation is individually rational for each owner, but all owners are worse off compared to non-delegation.
Keywords: L1; M2; 330; Strategic Delegation; Mergers; Oligopoly; Contests